The Effect of Laparoscopic Radical Hysterectomy Surgical Volume on Oncology Outcomes in Early-Stage Cervical Cancer - Li, Pengfei; Liu, Jiaqi; Wang, Li; Kang, Shang; Yang, Ying; Guo, Jianxin; Yao, Jilong; Lu, Anwei; Wang, Zhonghai; Lin, Bin; Li, Zhiqiang; Bin, Xiaonong; et al. (Frontiers in Surgery, 2021)
Purpose: To examine the association between surgical volume and surgical and oncological outcomes of women with stage IB1 cervical cancer who underwent laparoscopic radical hysterectomy (LRH). Methods: We retrospectively analyzed the oncological outcomes of 1137 patients with stage IB1 cervical cancer receiving LRH from 2004 to 2016. The surgical volume for each surgeon was defined as low (fewer than 50 surgeries, n=392[34.5%]), mid (51-100 surgeries, n=315[27.7%]), and high (100 surgeries or more, n=430[37.8%]). Surgical volume-specific survival was examined with Kaplan-Meier analysis, multivariable analysis and propensity score matching. Results: The operative times of the high-volume group (227.35±7.796 minutes) was significantly shorter than that of the low- (272.77±4.887 minutes, p<0.001) and mid-volume (255.86±4.981 minutes, p<0.001) groups. Blood loss in the high-volume group (169.42±8.714ml) was significantly less than that in the low-volume group (219.24±11.299 ml, p = 0.003). The 5-year DFS and OS in the low-volume, mid-volume and high-volume groups was similar (DFS: 91.9%, 86.7% and 89.2%, p=0.102; OS: 96.4%, 93.5% and 94.2%, p=0.192). Multivariable analysis revealed surgical volume was not an independent risk factor for OS or DFS. The rate of intraoperative and postoperative complications were similar among three groups (p=0.210). Conclusion: Surgical volume of LRH may not be a prognostic factor for patients with stage IB1 cervical cancer. Surgery at high-volume surgeon is associated with decreased operative time and blood loss.